Essays in Positive Economics - Hahn, F. H.; Friedman, Milton (Econometrica, 1954)
Stimulating, provocative, often infuriating, but well worth reading.—Peter Newman, Economica His critical blast blows like a north wind against the more pretentious erections of modern economics. It is however a healthy and invigorating blast, without malice and with a sincere regard for scientific objectivity.—K.E. Boulding, Political Science Quarterly Certainly one of the most engrossing volumes that has appeared recently in economic theory.—William J. Baumol, Review of Economics and Statistics